Implementation of Advanced Encryption Standard (AES) Algorithm for Employee Data Security at Binjai Religious Court - Silfani, Dilla (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In the digital era, data security in government institutions has become crucial, including at the Binjai Religious Court, which manages employee data in digital document form. Sensitive employee information such as identity, work history, and financial records is highly vulnerable to leakage and unauthorized access. To address this issue, this research implements the Advanced Encryption Standard (AES-128) algorithm as a data protection solution. The research methodology includes problem identification, literature study, system requirements analysis, design, implementation, and testing. The system was developed as a web-based application using PHP programming language, the CodeIgniter framework, and a MySQL database. AES is applied to encrypt and decrypt files in .docx and .xlsx formats. The test results show that encrypted files cannot be accessed without the correct key, while decrypted files can be fully restored to their original form. The encryption and decryption processes also run in relatively short times, making the system efficient and stable. In conclusion, the implementation of AES-128 successfully enhances the security of employee data at the Binjai Religious Court and can serve as a reference for other institutions in developing cryptography-based data security systems.